Dampak Perkembangan Pariwisata Terhadap Kondisi Sosial Budaya dan Ekonomi Masyarakat Samarinda - Fauzi, Muhammad Ibnu Faruk (TOBA: Journal of Tourism, Hospitality, and Destination, 2022)
This study aims to describe and analyze the impact of tourism development on the socio-cultural and economic community of Samarinda. This is based on the idea that until now tourism in Samarinda has not been able to create tourism characteristics in Samarinda even though many Samarinda tourist destinations have their own charm, as well as the impact that will be obtained by the development of tourism. Based on the objectives of this study includes several theories, concepts and literature studies referred to in the concept of tourism, the principles of development tourism, and the concept of tourism impact. Meanwhile, the research method used is a descriptive analysis of the socio-cultural and economic conditions of the Samarinda community. By answering the problem formulation of this study, obtained from data or information can then be classified into positive and negative impacts on the socio-cultural and economic life of the community, and contribute strategies to minimize the negative impact of tourism on society.